The cellular immune responsefrom vaginal mucosa in the vulvovaginitis - Giraldo, Paulo C; Feitoza, Sandra BN; Gonçalves, Ana KS; Cornetta, Maria da Conceição M; Eleutério Junior, José; Tristão, Andréia R (Brazilian Journal of Sexually Transmitted Diseases, 2006)
After the aids (acquired immunodeficiency syndrome) epidemic, the mechanisms of vaginal defense have been coated with special importance in the study ofthe genital feminine infections. The cellular immune response is perhaps one of the main protection mechanisms of the vaginal mucosa by means developmentof local immune response. There are many different defense cells (macrophages, lymphocytes, Langerhans cells, eosinophils and mastocytes) in the vaginalepithelium ready to be elicited. The lymphocytes are the main defense cells; they come from the basal plaque crossing the intercellular canals, preceded onlyby Langerhans cells and macrophages, in order to eradicate the invasive microorganisms. The defense cells control the bacterial and fungi growth, by meansof phagocytosis activation. If the cellular immune response fails, vaginal infections can occur. The authors revise the theme emphasizing the importance of theadequate immune response in the vaginal equilibrium.